Association between admission hyperglycaemia with in-hospital mortality rate in patients with hypertension and acute aortic dissection - Saimire Mutailifu; Qing Zhu; Xintian Cai; Mulalibieke Heizhati; Shasha Liu; Yujie Dang; Ting Wu; Jing Hong; Yue Lin; Nanfang Li (Journal of International Medical Research)
Objective Admission hyperglycaemia is recognized as a contributor to poor outcomes in patients with cardiovascular and cerebrovascular diseases. This study aimed to evaluate the association between admission hyperglycaemia and in-hospital mortality in patients with hypertension and acute aortic dissection (AAD). Methods Patients diagnosed with hypertension and AAD between 1 January 2010 and 1 March 2023 were enrolled into this retrospective observational study, and divided into two groups based on admission blood glucose levels (BGA): normoglycemia (BGA < 7.8 mmol/L) and hyperglycaemia (BGA ≥ 7.8 mmol/L). The outcome was all-cause in-hospital mortality, which was analysed using logistic regression to calculate odds ratios (ORs) and 95% confidence intervals (CIs). Results In total, 1239 patients were included (comprising 954 [77%] male patients; mean age, 53.0 years; and median BGA, 6.1 mmol/L). Logistic regression analysis showed that in-hospital mortality was 2.53 times greater for patients with hyperglycaemia versus the normoglycaemia group (95% CI 1.68, 3.80). This significant association persisted after adjustments for potential confounders (adjusted OR 2.45 [95% CI 1.58, 3.85]). Restricted cubic spline analysis revealed that the relationship between BGA and mortality reached statistical significance at BGA > 6.1 mmol/L. Stratified analysis and sensitivity analysis confirmed the robustness of this relationship. Conclusion Admission hyperglycaemia correlated with an elevated risk of in-hospital mortality in patients with hypertension and AAD, particularly BGA > 6.1 mmol/L, indicating that BGA level may be useful in identifying patients who are at an elevated risk of all-cause mortality.